PENGARUH LATIHAN SINGLE LEG SPEED HOP TERHADAP POWER OTOT TUNGKAI PADA CLUB FUTSAL PUTRA ABE JEMSI DURI BENGKALIS - M. Ridwan M. Ridwan; Zainur Zainur; Ali Mandan (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: The problem in this study is that there is still a lack of goal-shootingability, especially in leg muscle power because the Putra Abe Jemsi Duri futsal club,Bengkalis Regency has never done exercises to improve physical condition, especiallyleg muscle power. To fix this problem, the author provides a form of exercise thatincreases power, especially in the leg muscles, namely single-leg speed hop exercises.The title raised in this study is